Penggunaan Tepung Temulawak (Curcuma xanthorrhiza Roxb) Dan Jahe Merah (Zingiber officinale var. Rubrum) Dalam Ransum Terhadap Performa Pertumbuhan Dan Daya Cerna Ayam Petelur Jantan - Muiz, Abdul; Mozin, Selvy; Hafsah, Hafsah (Universitas Tadulako, 2022)
This study aims to determine the growth performance and nutritional digestibility of laying hens using curcuma and red ginger as feed additives. The research was conducted at the Teaching Farm, Faculty of Animal Husbandry and Fisheries, South Sibalaya Village, Tanambulava District. Sigi Regency, March 23 - May 03, 2020. The research design used a completely randomized design. The variables observed were growth and digestibility performance. Growth performance consisted of ration consumption, body weight gain, and ration consumption. Digestibility consists of digestibility of crude protein and crude fat. The results showed that the addition of curcuma flour at a level of 0.5% -1.5% can have a significant effect on body weight gain and crude protein digestibility (P>0.01) while the addition of red ginger at a level of 0.5% - 1.5% can have a significant effect on body weight gain, ration conversion, crude protein digestibility and crude fat digestibility (P>0.01). The conclusion from the results of the study that the performance of red ginger added at the level of 0.5%-1.5% was more effective in influencing growth and digestibility performance than that of curcuma.